2015
DOI: 10.1007/s12291-015-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Deficient Transferrin and Interleukin-6 as Predictors of Fibrosis in Alcohol Cirrhosis

Abstract: The severity of alcoholic cirrhosis depends on the presence of liver inflammation and fibrogenesis. Previous studies have hypothesized that carbohydrate deficient transferrin can be used as marker of liver impairment in alcoholic liver disease patients. The present study was designed to assess whether carbohydrate deficient transferrin is associated with procollagen III peptide and predict fibrosis in alcohol cirrhosis patients. We enrolled 48 patients with alcoholic cirrhosis and 38 healthy controls. Serum ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous reports have suggested the possibility of using selected interleukins as biochemical markers of cirrhosis. Nandeesha et al suggested that one of the predictors of fibrosis in alcoholic cirrhosis may include elevated interleukin-6 [18]. Yang et al investigated serum levels of FGF-21 in diagnosing nonalcoholic steatoheaptitis (NASH) and the critical stage of non-alcoholic fatty liver disease (NAFLD) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested the possibility of using selected interleukins as biochemical markers of cirrhosis. Nandeesha et al suggested that one of the predictors of fibrosis in alcoholic cirrhosis may include elevated interleukin-6 [18]. Yang et al investigated serum levels of FGF-21 in diagnosing nonalcoholic steatoheaptitis (NASH) and the critical stage of non-alcoholic fatty liver disease (NAFLD) [19].…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative, sandwich enzyme immunoassay technique was used to measures CDT from serum samples. [19] The assay was performed by ELISA (Enzyme-Linked Immuno-Sorbent Assay) technique (Tecan GENios ELISA reader, Austria GmbH, Austria), using Magellan software. The procedure was followed as per the protocol provided by the manufacturer (Cusabio, USA).…”
Section: Phase 1: Optimizationmentioning
confidence: 99%